Waterproof wear-resistant label and preparation process thereof

By using silicone-acrylate copolymer, nanosilica and dopamine modification technology in the adhesive of the label paper, a dynamic crosslinking network is formed, which solves the problem of insufficient waterproofness and wear resistance of the label paper, and achieves better adhesion and service life.

CN119592253AActive Publication Date: 2025-03-11SHANGHAI MINHAO PACKING MATERIALS CO LTD

Patent Information

Application Number
CN202510143784.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The existing label paper has poor waterproof performance and insufficient wear resistance, resulting in reduced adhesion and shortened service life in humid environments.

Method used

Using an adhesive containing a silicone-acrylate copolymer and nanosilica, a dynamic crosslinking network is formed to improve adhesion and wear resistance by introducing borate bonds and dopamine-modified nanosilica into the adhesive.

Benefits of technology

It significantly improves the waterproofness and wear resistance of label paper, ensuring that it can maintain good adhesion and service life in long-term humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a waterproof wear-resistant label and a preparation process thereof, and belongs to the technical field of label paper.The waterproof wear-resistant label comprises surface paper, an adhesive, a film coating layer and release bottom paper, the adhesive comprises the following raw materials in parts by mass: 60-80 parts of an acrylic monomer, 3-5 parts of a polyfunctional group crosslinking monomer, 6-10 parts of a siloxane-acrylate copolymer, 1-2 parts of an initiator, 5-8 parts of nano silicon dioxide and 50-60 parts of a solvent. And a molecular chain of the siloxane-acrylate copolymer contains a boric acid ester bond. A siloxane long chain in the siloxane-acrylate copolymer has low surface energy, can help to form a waterproof barrier, and can effectively prevent water from permeating into an interface between the label and a product, so that the waterproofness of the label is greatly improved; and a dynamic cross-linked network can be formed by introducing boric acid ester bonds, so that the stability is improved, the label structure is reinforced, the wear resistance is improved, and the label can be tightly attached to a base material in a long-term humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of label paper, and in particular relates to a waterproof and wear-resistant label and a preparation process thereof. Background Art

[0002] In modern packaging, label paper is an important material for information identification. It also has multiple functions such as brand promotion, anti-counterfeiting and functional protection. Therefore, it is widely used in many fields, such as food packaging, daily chemical product packaging and pharmaceutical packaging.

[0003] Among them, especially in food packaging and daily chemical product packaging, the products need to be in contact with moisture for a long time. For example, beer or other drinks are often cooled with ice water or refrigerated to improve the taste. After refrigeration, a large amount of water droplets will condense on the surface of the product at room temperature, or direct contact with ice water will damage the adhesive of the product label, causing its adhesion to drop significantly and damaging the product appearance; or the product needs to be in a humid environment, such as shower gel, shampoo or skin care products, which are stored in a high humidity environment for a long time. The moisture in the air will gradually penetrate into the label, causing an adverse effect on the label paper. At the same time, frequent handling may cause the label surface coating to peel off or the pattern to become blurred.

[0004] In order to solve these problems, the label materials widely used in the market currently usually have a waterproof coating on the surface of the label to enhance the waterproof performance of the label. However, the bonding force between this waterproof coating and the label paper is limited. When encountering a large amount of water penetration, the viscosity of the coating will decrease. In addition, the coating has poor wear resistance and is easily damaged by friction, which reduces the service life of the label. Summary of the invention

[0005] The purpose of the present invention is to provide a waterproof and wear-resistant coating and a preparation process thereof, so as to solve the problem that the label paper has poor waterproof performance and weak wear resistance.

[0006] The purpose of the present invention can be achieved by the following technical solutions: In a first aspect, the present invention provides a waterproof and wear-resistant label, comprising a face paper, an adhesive, a coating layer and a release backing paper, wherein the adhesive comprises the following raw materials in parts by weight: 60-80 parts of acrylic acid monomer; 3-5 parts of multifunctional cross-linking monomer; 6-10 parts of silicone-acrylate copolymer; 1-2 parts of initiator; 5-8 parts of nano silicon dioxide; 50-60 parts of solvent; The siloxane-acrylate copolymer contains borate bonds in the molecular chain.

[0007] Preferably, the acrylic monomer includes an acrylic soft monomer and an acrylic hard monomer in a mass ratio of (0.8-0.9):(0.1-0.2).

[0008] More preferably, the acrylic soft monomer includes a combination of one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, n-octyl methacrylate, isobornyl acrylate and octadecyl acrylate.

[0009] More preferably, the acrylic hard monomer includes a combination of one or more of methyl methacrylate, glycidyl methacrylate, ethyl methacrylate, acrylic acid and methacrylic acid.

[0010] Preferably, the multifunctional crosslinking monomer includes a combination of one or more of divinylbenzene, trimethylolpropane triacrylate, N,N'-methylenebisacrylamide and pentaerythritol tetraacrylate.

[0011] Preferably, the initiator includes a combination of one or more of benzoyl peroxide, di-tert-butyl peroxide, ammonium persulfate, azobisisobutyronitrile, benzoin ether and benzoin dimethyl ether.

[0012] Preferably, the solvent includes one of an alcohol solvent, a ketone solvent and an ether solvent.

[0013] More preferably, the alcohol solvent includes one of methanol, isopropanol, ethanol and n-butanol; the ketone solvent includes one of butanone, acetone, cyclohexanone and N-methylpyrrolidone; the ether solvent includes one of ethylene glycol monobutyl ether, propylene glycol monomethyl ether and anisole.

[0014] By adopting the above technical solution, acrylic soft monomer and acrylic hard monomer provide good adhesion performance for label paper under the action of multifunctional cross-linking monomer, and the addition of nano-silica can enhance the wear resistance of the label. In order to enhance the waterproofness of the label, a siloxane-acrylate copolymer is added to the adhesive, in which the siloxane chain segment is grafted on the molecular chain of the acrylate, which can greatly improve the compatibility between the siloxane chain segment and the acrylic matrix, and is conducive to the uniform dispersion of the siloxane chain segment and the formation of a uniform and dense protective film. The formed protective film can effectively prevent moisture from penetrating into the interface between the label and the product, and improve the waterproof ability of the label. Moreover, the low surface energy of the siloxane itself makes the formed adhesive layer not easily wetted by water, further enhancing the waterproof effect. In addition, the molecular chain length of the siloxane-acrylate copolymer can give the adhesive good flexibility, and the acrylate segment can ensure the cohesive force of the adhesive, so that the label paper after waterproofing can also be well adhered to products of different materials.

[0015] At the same time, the siloxane-acrylate copolymer has a longer molecular chain segment. Compared with general siloxanes, such as silane coupling agents, the waterproof barrier formed can better block long-term moisture erosion and can also greatly optimize the compatibility with the acrylic matrix.

[0016] However, although adding only siloxane-acrylate copolymer can improve the cohesive force, it is easy to cause the interaction force between the molecular chains inside the adhesive to be enhanced, which is higher than the interaction force between the adhesive and the substrate, which will reduce the peel strength between the label and the substrate to a certain extent. At the same time, the introduction of the long siloxane chain will affect the stability of the formed adhesive layer, causing some material defects and affecting the service life of the label. In order to improve this problem, the molecular chain of the siloxane-acrylate copolymer of the present invention also contains borate bonds.

[0017] The introduction of borate bonds can significantly improve the bonding performance of the adhesive and help form a more stable cross-linked network structure. It can interact with the siloxane segments. The formed Si-OB cross-linked network can effectively improve the heat resistance and stability of the adhesive and improve the structural defects caused by long-chain siloxanes. The borate bonds can form a dynamic cross-linked network, enhance the bonding strength with the substrate and the coating layer, and also bring a certain self-healing ability to resist external pressure.

[0018] Preferably, the raw materials of the siloxane-acrylate copolymer include an acrylic acid compound, a monoacrylate-terminated polysiloxane and an aldehyde-phenylboronic acid compound in a mass ratio of 100:(10-15):(2-3).

[0019] Preferably, the acrylic compound includes at least one hydroxy acrylic compound; the hydroxy acrylic compound includes one or a combination of hydroxyethyl methacrylate and hydroxypropyl methacrylate.

[0020] Preferably, the acrylic compound may further include a combination of one or more of methyl methacrylate, butyl acrylate, isooctyl acrylate, methacrylic acid and isobornyl acrylate.

[0021] Preferably, the formylphenylboronic acid compound includes one or more of 4-formylphenylboronic acid, 3-formylphenylboronic acid and 4-formyl-3,5-dimethoxyphenylboronic acid.

[0022] By adopting the above technical scheme, the hydroxy acrylic compound adds a new polar group to the obtained acrylate copolymer, which can help polymerize with polysiloxane and formaldehyde phenylboronic acid compounds. The final siloxane-acrylate copolymer contains long-chain siloxane segments, which can form a uniform and dense waterproof barrier, thereby improving the waterproofness of the entire label paper.

[0023] The addition of aldehyde phenylboronic acid compounds provides the copolymer with a dynamic covalent borate bond, which can coordinate the long siloxane chain. The characteristics of the dynamic bond enable the borate bond to react with other oxygen-containing functional groups in the matrix to form reversible cross-linking points, which not only endows the material with self-healing capabilities, but also helps improve structural defects and improve the adhesion of the label, allowing the label to be tightly attached to the substrate even in a long-term humid environment.

[0024] Preferably, the siloxane-acrylate copolymer is prepared according to the following method: Adding an aldehyde phenylboronic acid compound to thionyl chloride, raising the temperature to 70-80° C., and reflux reacting for 10-12 hours to obtain a pre-reaction monomer; Raising the temperature of the solvent to 80-85° C., adding an acrylic compound, a monoacrylate-terminated polysiloxane and an initiator in a nitrogen atmosphere, stirring and reacting for 2-3 hours, and then continuing to add the initiator, reacting for 2-3 hours, and drying to obtain a siloxane-acrylate prepolymer; Add siloxane-acrylate prepolymer and pre-reaction monomer to the solvent respectively, mix the obtained solutions, add catalyst, raise the temperature to 80-90° C., keep the temperature to react for 10-12 hours, and finally obtain siloxane-acrylate copolymer through filtering, washing and drying.

[0025] Preferably, the initiator and the initiator in the adhesive raw material are the same substance.

[0026] Preferably, the solvent includes a combination of one or more of toluene, xylene and N,N-dimethylformamide.

[0027] Preferably, the catalyst comprises one of p-toluenesulfonic acid, sulfuric acid and hydrochloric acid.

[0028] By adopting the above technical scheme, the acrylic acid compound is first polymerized under the action of an initiator and reacts with the monoacrylate-terminated polysiloxane to form a connection, and then undergoes an acetal reaction with the monomer compound formed by the aldehyde phenylboronic acid compound to form a borate ester bond.

[0029] Preferably, dopamine is grafted onto the surface of the nano-silicon dioxide; the mass ratio of the nano-silicon dioxide to dopamine is 1:(1.5-2.5).

[0030] Preferably, nano-silicon dioxide grafted dopamine is prepared according to the following method: Dopamine is dissolved in Tris buffer, nano-silica is added, and the mixture is stirred at room temperature for 6 to 8 hours. Finally, the nano-silica grafted dopamine is obtained through centrifugal separation, washing and drying.

[0031] By adopting the above technical solution, the addition of nano-silica inorganic filler can improve the wear resistance of label paper, but due to the strong flexibility of siloxane-acrylate copolymer, the wear resistance of label paper decreases accordingly. Therefore, the present invention also modifies the nano-silica and grafts dopamine on the surface.

[0032] The molecular structure of dopamine contains amino and catechol groups, among which the amino group imparts strong reactivity, thereby improving the dispersibility of nano-silica in the acrylic matrix. It can also react and cross-link with the acrylic matrix to enhance the cross-linking density of the adhesive. In the process of compounding the adhesive and the coating layer, the adhesive containing dopamine can better penetrate into the surface micropores of the coating layer to form a stronger interface bond, strengthen the label paper, and improve the wear resistance of the label paper.

[0033] Moreover, the catechol groups of dopamine can form strong bonds with the surfaces of various materials, and cooperate with the borate bonds in the siloxane-acrylate copolymer to dynamically cross-link in a wet environment, providing stronger and more durable adhesion in a humid or underwater environment.

[0034] Preferably, the coating layer includes one of a PET film, a PP film and a PE film.

[0035] In a second aspect, the present invention provides a process for preparing a waterproof and wear-resistant label, comprising the following process steps: S1. Weigh the raw materials of the adhesive according to the corresponding mass parts, stir and mix for 3 to 4 hours to obtain the adhesive; S2. Applying an ink layer on one side of the tissue paper, applying the adhesive on one side of the tissue paper containing the ink layer after drying, and then drying and hot pressing a composite coating layer by a laminating machine; S3. Apply adhesive on the other side of the face paper, adhere it to the release backing paper after drying, and obtain a waterproof and wear-resistant label.

[0036] Beneficial effects of the present invention: 1. The adhesive of the waterproof and wear-resistant label obtained by the present invention contains a siloxane-acrylate copolymer. The long chain of siloxane can help form a waterproof barrier. The low surface energy of siloxane itself also makes it difficult for the formed adhesive layer to be wetted by water, thereby effectively preventing moisture from penetrating into the interface between the label and the product, greatly improving the waterproofness of the label. In order to compensate for the problem of decreased adhesion performance caused by the low intermolecular force of siloxane, a borate bond is introduced into the molecular chain of the siloxane-acrylate copolymer, which can form a dynamic cross-linking network, improve stability, and improve structural defects. The label can also be tightly attached to the substrate in a long-term humid environment.

[0037] 2. In order to further improve the wear resistance and water resistance of the label, the nano-silica is also subjected to a grafting modification treatment in the present invention. The grafted dopamine can increase the bonding force with the coating layer, strengthen the label, and improve the wear resistance of the label. At the same time, the catechol group in dopamine can also cooperate with the borate bond in the siloxane-acrylate copolymer to dynamically cross-link in a humid environment, thereby providing the label with a more stable and lasting adhesion in a humid environment. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Preparation Example 1 Preparation Example 1-1, a siloxane-acrylate copolymer, was prepared according to the following method: Add 2.5 g of 4-formylphenylboronic acid to 25 mL of thionyl chloride, raise the temperature to 70° C., and reflux for 12 h to obtain a pre-reaction monomer; The temperature of 250 mL toluene was raised to 85°C, and 100 g of acrylic acid compound, 12 g of monoacrylate-terminated polysiloxane (model: Silok®3821F3) and 0.3 g of ammonium persulfate were added in a nitrogen atmosphere, wherein the acrylic acid compound was a mixture of hydroxyethyl methacrylate and butyl acrylate in a mass ratio of 6:4, and stirred for reaction for 2 h, and then 0.1 g of ammonium persulfate was added, and the reaction was continued for 2 h, and then dried to obtain a siloxane-acrylate prepolymer; The obtained siloxane-acrylate prepolymer and pre-reaction monomer were added to toluene respectively to prepare solutions with a mass fraction of 50%, the obtained solutions were mixed, 0.3 g of p-toluenesulfonic acid was added, the temperature was increased to 85°C, the reaction was kept warm for 12 hours, and finally the siloxane-acrylate copolymer was obtained by filtering, washing and drying.

[0040] Preparation Example 1-2, a siloxane-acrylate copolymer, is different from Preparation Example 1-1 only in that the added amount of 4-formylphenylboric acid is 2 g; the added amount of monoacrylate-terminated polysiloxane is 10 g.

[0041] Preparation Example 1-3, a siloxane-acrylate copolymer, is different from Preparation Example 1-1 only in that the added amount of 4-formylphenylboronic acid is 3 g; the added amount of monoacrylate-terminated polysiloxane is 15 g.

[0042] Preparation Example 1-4, a siloxane-acrylate copolymer, is different from Preparation Example 1-1 only in that the amount of monoacrylate-terminated polysiloxane added is 5 g.

[0043] Preparation Example 1-5, a siloxane-acrylate copolymer, is different from Preparation Example 1-1 only in that the amount of monoacrylate-terminated polysiloxane added is 20 g.

[0044] Preparation Example 1-6, a siloxane-acrylate copolymer, was prepared according to the following method: The temperature of 250 mL of toluene was raised to 85°C, and 100 g of acrylic acid compound, 12 g of monoacrylate-terminated polysiloxane (model: Silok®3821F3) and 0.3 g of ammonium persulfate were added in a nitrogen atmosphere, wherein the acrylic acid compound was a mixture of hydroxyethyl methacrylate and butyl acrylate in a mass ratio of 6:4. After stirring and reacting for 2 h, 0.1 g of ammonium persulfate was added, and the reaction was continued for 2 h. After drying, a siloxane-acrylate copolymer was obtained.

[0045] Preparation Example 1-7, an acrylic acid ester copolymer, was prepared according to the following method: Add 2.5 g of 4-formylphenylboronic acid to 25 mL of thionyl chloride, raise the temperature to 70° C., and reflux for 12 h to obtain a pre-reaction monomer; Raise the temperature of 250 mL toluene to 85° C., add 100 g of acrylic acid compound and 0.2 g of ammonium persulfate in a nitrogen atmosphere, wherein the acrylic acid compound is a mixture of hydroxyethyl methacrylate and butyl acrylate in a mass ratio of 6:4, stir and react for 2 hours, then continue to add 0.1 g of ammonium persulfate, react for 2 hours, and then dry to obtain an acrylic acid prepolymer; The obtained acrylate prepolymer and pre-reaction monomer were added to toluene respectively to prepare solutions with a mass fraction of 50%. The obtained solutions were mixed, 0.3 g of p-toluenesulfonic acid was added, the temperature was raised to 85° C., the reaction was kept warm for 12 hours, and finally the acrylate copolymer was obtained by filtering, washing and drying.

[0046] Preparation Example 1-8, an acrylic acid ester copolymer, was prepared according to the following method: The temperature of 250 mL of toluene was raised to 85° C., and 100 g of an acrylic acid compound and 0.2 g of ammonium persulfate were added in a nitrogen atmosphere, wherein the acrylic acid compound was a mixture of hydroxyethyl methacrylate and butyl acrylate in a mass ratio of 6:4. After stirring and reacting for 2 hours, 0.1 g of ammonium persulfate was added, and the mixture was reacted for 2 hours and dried to obtain an acrylic acid ester copolymer.

[0047] Preparation Example 2 Preparation Example 2-1: A nano-silicon dioxide is subjected to grafting modification treatment according to the following method: 20 g of dopamine was dissolved in 600 mL of Tris buffer, 10 g of nano-silica (average particle size of 30 nm) was added, and the reaction was stirred at room temperature for 6 h. Finally, the nano-silica grafted dopamine was obtained by centrifugation, washing and drying.

[0048] Example Example 1, a waterproof and wear-resistant label, is prepared according to the following process steps: S1. Weigh 70 parts of acrylic acid monomer, 4 parts of trimethylolpropane triacrylate, 8 parts of the siloxane-acrylate copolymer prepared in Preparation Example 1-1, 1 part of azobisisobutyronitrile, 6 parts of nano-silicon dioxide (average particle size of 30 nm) and 55 parts of isopropanol, and stir and mix for 4 hours to obtain an adhesive; wherein the acrylic acid monomer is a mixture of ethyl acrylate and methyl methacrylate in a mass ratio of 0.8:0.2; S2. Applying an ink layer on one side of the tissue paper, applying the obtained adhesive on the side of the tissue paper containing the ink layer after drying, and then drying and hot pressing a PET film (thickness of 15 μm) by a laminating machine; S3. Apply adhesive on the other side of the face paper, adhere it to the release backing paper after drying, and obtain a waterproof and wear-resistant label.

[0049] Embodiment 2 and Embodiment 3 are waterproof and wear-resistant labels. The difference from Embodiment 1 is that the raw material ratio of the adhesive is adjusted, as shown in Table 1: Table 1 Adhesive formulations for Examples 1 to 3

[0050] The acrylic acid monomer of Example 2 is a mixture of ethyl acrylate and methyl methacrylate in a mass ratio of 0.8:0.2; and the acrylic acid monomer of Example 3 is a mixture of ethyl acrylate and methyl methacrylate in a mass ratio of 0.9:0.1.

[0051] Example 4, a waterproof and wear-resistant label, is different from Example 1 only in that the amount of the silicone-acrylate copolymer prepared in Preparation Example 1-1 added is 6 parts.

[0052] Example 5, a waterproof and wear-resistant label, is different from Example 1 only in that the amount of the silicone-acrylate copolymer prepared in Preparation Example 1-1 added is 10 parts.

[0053] Example 6, a waterproof and wear-resistant label, is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the siloxane-acrylate copolymer prepared in Preparation Example 1-2.

[0054] Example 7, a waterproof and wear-resistant label, is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the siloxane-acrylate copolymer prepared in Preparation Example 1-3.

[0055] Example 8, a waterproof and wear-resistant label, is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the siloxane-acrylate copolymer prepared in Preparation Example 1-4.

[0056] Example 9, a waterproof and wear-resistant label, is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the siloxane-acrylate copolymer prepared in Preparation Example 1-5.

[0057] Example 10, a waterproof and wear-resistant label, is different from Example 1 only in that the nano-silicon dioxide in Example 1 is replaced by an equal amount of nano-silicon dioxide prepared in Preparation Example 2-1.

[0058] Comparative Example Comparative Example 1 is a waterproof and wear-resistant label, which is different from Example 1 only in that the amount of the silicone-acrylate copolymer prepared in Preparation Example 1-1 added is 3 parts.

[0059] Comparative Example 2 is a waterproof and wear-resistant label, which is different from Example 1 only in that the amount of the silicone-acrylate copolymer prepared in Preparation Example 1-1 added is 12 parts.

[0060] Comparative Example 3 is a waterproof and wear-resistant label, which is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the siloxane-acrylate copolymer prepared in Preparation Example 1-6.

[0061] Comparative Example 4 is a waterproof and wear-resistant label, which is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the acrylate copolymer prepared in Preparation Example 1-7.

[0062] Comparative Example 5 is a waterproof and wear-resistant label, which is different from Example 1 only in that the siloxane-acrylate copolymer prepared in Preparation Example 1-1 is replaced by an equal amount of the acrylate copolymer prepared in Preparation Example 1-8.

[0063] Comparative Example 6 is a waterproof and wear-resistant label, which is different from Example 1 only in that an equal amount of 3-aminopropyltriethoxysilane is used to replace the siloxane-acrylate copolymer prepared in Preparation Example 1-1.

[0064] Performance testing Adhesion test: The labels obtained in the examples and comparative examples were adhered to a PET plate, hot-pressed for 1 hour and then naturally cooled, and the peeling force of the film was tested; Waterproof test: Place the adhesion test sample in an ice-water mixture for 30 minutes, and continue to test the peeling force of the film; Abrasion resistance test: According to the relevant records in GB / T 6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes", the surface abrasion resistance of the labels of the embodiments and comparative examples was tested.

[0065] The above test results are shown in Table 2: Table 2 Performance test results

[0066] According to Example 1, Example 8, Example 9 and Comparative Example 4, it can be seen that the peeling force of Example 8, Example 9 and Comparative Example 4 decreases after immersion in ice water, and the decrease in Comparative Example 4 is the most obvious. The reason is that the difference between Example 8, Example 9 and Comparative Example 4 compared with Example 1 is that the content of the siloxane segment in the added siloxane-acrylate copolymer is adjusted outside the required range, wherein the amount of the added siloxane segment is reduced in Example 8, and accordingly, the waterproofness of the adhesive decreases accordingly. In a humid environment, the adhesive is greatly affected by moisture and the adhesion decreases. The acrylate copolymer used in Comparative Example 4 does not contain siloxane segments, and the performance decreases more significantly. In Example 9, the content of monoacrylate-terminated polysiloxane in the siloxane-acrylate copolymer is increased, and the content of the siloxane segment is increased, and the introduction of a large number of low surface energy segments will reduce the adhesion of the adhesive itself.

[0067] Combining Example 1 and Example 10, it can be seen that the adhesion, water resistance and hardness of Example 10 are all enhanced compared with Example 1. The reason is that the nano-silica particles in Example 10 are treated with dopamine grafting modification, and the introduction of polar groups strengthens the bonding force between the adhesive and the substrate, and the catechol group can cooperate with the borate bond in the siloxane-acrylate copolymer to form a denser dynamic cross-linking network, which can not only improve the wear resistance, reduce the probability of water penetration, but also improve the adhesion under humid conditions.

[0068] Combining Example 1 and Comparative Example 3, it can be seen that the adhesion, water resistance and hardness of Comparative Example 3 are all lower than those of Example 1. The reason is that no borate bond is introduced into the siloxane-acrylate copolymer in Comparative Example 3, so the structural defects and stability reduction caused by the long siloxane chain will reduce the adhesion of the adhesive, and the adhesive will be more likely to fail after being soaked in ice water. At the same time, the lack of borate bonds also affects the cross-linking network in the adhesive, which will reduce the bonding force between the face paper and the coating layer, reduce the reinforcement effect on the label, and reduce the wear resistance.

[0069] Combining Example 1 and Comparative Example 6, it can be seen that the adhesion of Comparative Example 6 after immersion in ice water is significantly reduced, indicating that the waterproofness of Comparative Example 6 is significantly reduced compared with Example 1. The reason is that in Comparative Example 6, the siloxane-acrylate copolymer is replaced by an aminosilane coupling agent. Under natural conditions, the addition of the silane coupling agent does not affect the adhesion of the adhesive. However, compared with the long chain of siloxane, the siloxane chain segment in the silane coupling agent is short, and it is difficult to form a tight waterproof barrier. Under long-term immersion, the adhesion of the adhesive will be significantly reduced, and the molecular weight of the silane coupling agent is low. The adhesive layer formed after combining with the coating layer does not enhance the reinforcement effect on the label and the enhancement of wear resistance.

[0070] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A waterproof and wear-resistant label, comprising a face paper, an adhesive, a coating layer and a release backing paper, characterized in that: The adhesive comprises the following raw materials in parts by weight: 60-80 parts of acrylic acid monomer; 3-5 parts of multifunctional cross-linking monomer; 6-10 parts of silicone-acrylate copolymer; 1-2 parts of initiator; 5-8 parts of nano silicon dioxide; 50-60 parts of solvent; The molecular chain of the silicone-acrylate copolymer contains a borate ester bond; The raw materials of the siloxane-acrylate copolymer include acrylic acid compound, monoacrylate-terminated polysiloxane and aldehyde-phenylboronic acid compound in a mass ratio of 100:(10-15):(2-3).

2. The waterproof and wear-resistant label according to claim 1, characterized in that: The acrylic monomers include acrylic soft monomers and acrylic hard monomers in a mass ratio of (0.8-0.9):(0.1-0.2).

3. The waterproof and wear-resistant label according to claim 1, characterized in that: The multifunctional cross-linking monomer includes one or more of divinylbenzene, trimethylolpropane triacrylate, N,N'-methylenebisacrylamide and pentaerythritol tetraacrylate.

4. The waterproof and wear-resistant label according to claim 1, characterized in that: The acrylic compound includes at least one hydroxy acrylic compound; the hydroxy acrylic compound includes one or a combination of hydroxyethyl methacrylate and hydroxypropyl methacrylate.

5. The waterproof and wear-resistant label according to claim 1, characterized in that: The formylphenylboronic acid compound includes one or more of 4-formylphenylboronic acid, 3-formylphenylboronic acid and 4-formyl-3,5-dimethoxyphenylboronic acid.

6. The waterproof and wear-resistant label according to claim 1, characterized in that: The siloxane-acrylate copolymer is prepared according to the following method: Adding an aldehyde phenylboronic acid compound to thionyl chloride, raising the temperature to 70-80° C., and reflux reacting for 10-12 hours to obtain a pre-reaction monomer; Raising the temperature of the solvent to 80-85° C., adding an acrylic compound, a monoacrylate-terminated polysiloxane and an initiator in a nitrogen atmosphere, stirring and reacting for 2-3 hours, and then continuing to add the initiator, reacting for 2-3 hours, and drying to obtain a siloxane-acrylate prepolymer; Add siloxane-acrylate prepolymer and pre-reaction monomer to the solvent respectively, mix the obtained solutions, add catalyst, raise the temperature to 80-90° C., keep the temperature to react for 10-12 hours, and finally obtain siloxane-acrylate copolymer through filtering, washing and drying.

7. The waterproof and wear-resistant label according to claim 1, characterized in that: Dopamine is also grafted onto the surface of the nano-silicon dioxide; the mass ratio of the nano-silicon dioxide to dopamine is 1:(1.5-2.5).

8. The waterproof and wear-resistant label according to claim 1, characterized in that: The coating layer includes one of a PET film, a PP film and a PE film.

9. A process for preparing a waterproof and wear-resistant label according to any one of claims 1 to 8, characterized in that: The process steps include: S1. Weigh the raw materials of the adhesive according to the corresponding mass parts, stir and mix for 3 to 4 hours to obtain the adhesive; S2. Applying an ink layer on one side of the tissue paper, applying the adhesive on one side of the tissue paper containing the ink layer after drying, and then drying and hot pressing a composite coating layer by a laminating machine; S3. Apply adhesive on the other side of the face paper, adhere it to the release backing paper after drying, and obtain a waterproof and wear-resistant label.

Citation Information

Patent Citations

  • Composition for the production of pressure-sensitive adhesives

    CN106967375A

  • Self-repairing antioxidant hydrogel based on boric acid ester bond

    CN110372828A

  • Preparation process of waterproof wear-resistant self-adhesive label

    CN116200139A

  • Self-cleaning wear-resistant fabric, preparation method and vamp

    CN117188173A

  • Spraying type anti-fogdrop functional repair liquid and preparation method thereof

    CN118530639A

Cited By

  • High-temperature-resistant waterproof PET label and preparation process thereof

    CN120564523A

  • Reversible cross-linked paper coating and repulp switching process

    CN120925355A